Enhanced climate instability in the North Atlantic and southern Europe during the Last Interglacial. Issue 1 (December 2018) - Tzedakis, P.; Drysdale, R.; Margari, V.; Skinner, L.; Menviel, L.; Rhodes, R.; Taschetto, A.; Hodell, D.; Crowhurst, S.; Hellstrom, J.; Fallick, A.; Grimalt, J.; et al.
Abstract Considerable ambiguity remains over the extent and nature of millennial/centennial-scale climate instability during the Last Interglacial (LIG). Here we analyse marine and terrestrial proxies from a deep-sea sediment sequence on the Portuguese Margin and combine results with an intensively dated Italian speleothem record and climate-model experiments. The strongest expression of climate variability occurred during the transitions into and out of the LIG. Our records also document a series of multi-centennial intra-interglacial arid events in southern Europe, coherent with cold water-mass expansions in the North Atlantic. The spatial and temporal fingerprints of these changes indicate a reorganization of ocean surface circulation, consistent with low-intensity disruptions of the Atlantic meridional overturning circulation (AMOC). The amplitude of this LIG variability is greater than that observed in Holocene records. Episodic Greenland ice melt and runoff as a result of excess warmth may have contributed to AMOC weakening and increased climate instability throughout the LIG. It is important to establish a baseline for natural climate variability under relatively warm conditions. Here we show that the Last Interglacial in the North Atlantic and southern Europe was characterized by enhanced climate instability relative to the pre-industrial Holocene.